Economic and health prospects and challenges of kombucha in Indonesia - Gunawan, William Ben; Gunawan, Alexander Ivan (Proceeding International Conference on Religion, Science and Education, 2025)
Economic growth always involves various aspects of the economy, one of which is the food and beverage industry. Kombucha, a globally consumed fermented beverage, has gained remarkable popularity among health-conscious individuals due to its slightly sweet and sour taste. Moreover, the process of crafting kombucha is relatively simple and practical, making kombucha a potentially lucrative product for businesses. Not only does kombucha offer health advantages and commercial viability, but it also holds promise for innovation in industry and the creative economy, opening the doors for the creation of various derivative products. However, the application of kombucha in Indonesia faces several challenges. This review seeks to examine the prospects and challenges of kombucha products in Indonesia both in terms of economy and health. A comprehensive review of national and international literature has been performed, presenting the idea of economic and health prospects and challenges of kombucha in Indonesia. Based on the contents, we propose that the application of kombucha in Indonesia is likely to bring more benefits (both health and economic) than its adverse health effects. The trend of kombucha beverage products in Indonesia is still constrained by several regulatory restrictions and halal aspects. Kombucha has advantages both in terms of affordable production costs and by-products of the kombucha fermentation process that can be applied in various industries as well as various health benefits of kombucha. Health claims on kombucha products will be better if accompanied by halal certification so that these benefits can be felt by the Indonesian people at large. Related to this, the author supports efforts to study and research kombucha products in more depth to provide excellence and benefits to the people of Indonesia. Various local foods, herbs, and resources in Indonesia can be used as the main ingredients of kombucha, so it becomes very interesting to explore.